Comparison of knowledge levels between boarding and non-boarding high school students in selecting rapid orthodontic care operators in Biringkanaya District, Makassar City: Perbandingan tingkat pengetahuan siswa SMA boarding dan non-boarding dalam pemilihan operator perawatan ortodonti cekat di Kecamatan Biringkanaya Kota Makassar - Zilal Islamy Paramma; Nasyrah Hidayati; Karima Qurnia Mansjur; Khoisah Ummi Utami; Rifaat Nurrahma (Makassar Dental Journal PDGI Makassar, 2026)
The high prevalence of malocclusion has led to an increased demand for fixed orthodontic treatment. This phenomenon is exploited by non-professional practitioners, which risks harming patients if the choice of practitioner is inappropriate; therefore, it is necessary to determine the level of knowledge underlying decision-making, taking into account differences in environment and access to information between boarding and non-boarding secondary school students, by comparing the level of knowledge of boarding and non-boarding secondary school students in Makassar regarding the selection of fixed orthodontic treat-ment practitioners. Using a quantitative method and an analytical observational design via a cross-sectional study approach, 150 respondents (75 boarding stu-dents and 75 non-boarding students) were involved in Biringkanaya District, Makassar City. Data were collected using a questionnaire and analysed using an independent samples t-test, which showed that the mean knowledge level of non-boarding students (62.17) fell into the ‘adequate’ category, whilst that of boarding students (52.03) fell into the ‘inadequate’ category. Statistical analysis revealed a significant level of 0.000 (p<0.05), proving a significant difference in knowledge levels between the two groups. It was concluded that non-boarding students possess a higher level of knowledge regarding the selection of fixed orthodontic appliances.